The changes in oxidative and antioxidative systems in experimental liver ischemia reperfusion damage - Ilhan, Nevin; Halifeoglu, Ihsan; Ilhan, Necip (My University, 2000)
Reperfusion-induced oxygen attack following ischemia increases mitocondrial respiration and production of superoxide radicals. As a result, mechanisms responsible for scavenging free radicals may not be sufficient Subsequently, increased lipid peroxidation in enzyme systems and free radical formation may ensue. In this study, we aimed to examine oxidant and antioxidant systems in experimentally induced ischemia-reperfusion (I-R) in Guinea pig liver model The levels of plasma malondialdehyde (MDA), a product of lipid peroxidation, and antioxidant enzymes, superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) in erythrocytes were analyzed. A total of 31 female Guinea pigs were divided into 4 groups; Sham (Group 1), Ischemia-reperfusion (Group 2), Ischemia-Reperfusion + SOD (Group 3) and Ischemia-Reperfusion+Allopurinol (Group 4). There was a statistically significant increase (p<0.05) in plasma MDA levels in Groups 2, 3 and 4 compared to Group 1. However, there was a significant reduction of plasma MDA levels following SOD and Allopurinol compared to Group 2. Superoxide dismutase and GSH-Px levels showed a significant reduction in Groups 2, 3 and 4 compared to sham group (Groupl). A slight increase in SOD levels in antioxidant receiving Groups (3 and 4) was observed when compared to Group 2. There was a statistically significant (p<0.05) increase in GSH-Px levels in SOD and allopunnol treated Groups (3 and 4) with respect to Group 2. In conclusion, increase in oxidative damage causes reduction in antioxidant capacity and the use of of antioxidant agents can prevent oxidative damage in vitro.
Keywords: Antioxidants; Ischemia-reperfusion; MDA